1984
DOI: 10.1037/0735-7044.98.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic mediation of spatial memory in the preweanling rat: Application of the radial arm maze paradigm.

Abstract: These experiments assessed spatial memory capabilities in the developing rat by the radial arm maze paradigm. Subjects were trained and tested in the maze beginning at 16 days until they were 25 days of age. Results showed that animals that received training performed significantly better than those naive to the task, and better than chance, which suggests an early capacity for this type of learning. The second experiment investigated the neural mechanism that underlies spatial memory at this age as measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 23 publications
6
34
0
Order By: Relevance
“…Although several studies have shown that early spatial experience plays a signi®cant role in later performance on spatial navigation tasks (e.g., Cramer et al, 1988;Rauch & Raskin, 1984), this presents an interesting paradox concerning the development of memory, infantile amnesia. Memories for events learned in infancy are likely to be forgotten more rapidly than those formed in adulthood (cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several studies have shown that early spatial experience plays a signi®cant role in later performance on spatial navigation tasks (e.g., Cramer et al, 1988;Rauch & Raskin, 1984), this presents an interesting paradox concerning the development of memory, infantile amnesia. Memories for events learned in infancy are likely to be forgotten more rapidly than those formed in adulthood (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Spear & Riccio, 1994). With the establishment of spatial navigation in the preweanling animal, using the Morris water maze and the results of the radial arm maze studies (Cramer et al, 1988;Rauch & Raskin, 1984), a logical question to address is how well the rat pup retains its memory for spatial information. Of the limited ontogenetic Morris water maze studies conducted, Brown and Kraemer's (1997) work is the only one that systematically examined spatial retention in immature rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Schenk (1985), on the other hand, 32-to 35-day-old animals can orientate using distal information. In learning on a radial maze, developmental studies show that young, recently weaned rats attain performances equivalent to adults (Olton & Schlosberg, 1978, Rauch & Raskin, 1984. However, in these studies, the authors used a nonconfinement procedure that revealed little about the type of information used by the subject to perform the task.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Rauch and Raskin (1984) has demonstrated the beneficial effects of juvenile training in preweanling rats. In this report, training on a spatial navigation task from p16 to p20 resulted in water maze performance that was significantly better than chance as well as significantly better than naïve animals.…”
mentioning
confidence: 99%